Padronização do extrato seco de Miconia albicans (sw.) Triana (Melastomataceae) e avaliação da atividade antioxidante - Couto, Luzi Paula da Silva Marins (2018)
Miconia albicans, popularly known as "canela-de-velho", "quaresmeira-de-flor-branca", "paude-tucano", is found in several regions of Brazil, predominantly in the Cerrado. In the literature, some pharmacological activities attributed to this species are reported, such as: antimalarial, antitumor, analgesic, and antifungal. In folk medicine, this species is used to treat arthritis and arthritis. The objective of this work was to standardize the dry extract of M. albicans (DEMA) and evaluate its antioxidant activity. In the characterization of DEMA, phytochemical screening, High Efficiency Liquid Chromatography (HPLC) and total phenol and flavonoid content were performed to characterize DEMA. In the evaluation of the antioxidant activity, in vitro, the tests of 2,2-diphenyl-1-picrylhydrazila (DPPH), 2,2'azinobis (3-ethylbenzthiazoline6-sulfonic acid (ABTS)), (NO), inhibition of lipid peroxidation (TBARS), iron reduction potential (FRAP) and chelating activity. The results were expressed as mean ± SEM and analyzed by analysis of variance followed by the Tukey test; p <0.05 was considered significant. The contents of total phenols and flavonoids in the extract were 551,300 ± 3,72 mg of gallic acid equivalents / g of extract and 367,193 ± 10,52 mg of catechin equivalents / g of extract, respectively. In the chromatographic profile of DEMA, quercetin and rutin were identified. DPPH (IC50 = 61.2284 μg / mL) was observed to decrease as well as increase in the ABTS moiety reduction, increase in the reduction potential by the FRAP assay and increase in NO reduction. In addition to reducing spontaneous lipid peroxidation (IC 50 = 1619.210526 μg / mL) in vitro, DEMA showed no chelating activity. At the same time, the results obtained by the DEMA showed antioxitant activity.